IL-23 Enhances C-Fiber-Mediated and Blue Light-Induced Spontaneous Pain in Female Mice - Ji, Jasmine; He, Qianru; Luo, Xin; Bang, Sangsu; Matsuoka, Yutaka; McGinnis, Aidan; Nackley, Andrea G.; Ji, Ru-Rong (Frontiers in Immunology, 2021)
The incidence of chronic pain is especially high in women, but specific pain signaling mechanisms in females remain poorly understood. Interleukin-23 (IL-23) is a pro-inflammatory cytokine and plays an active role in inflammatory and neuropathic pain. In this study, we examined the IL-23 involvement in sexual dimorphism of pain, using both behavioral and optogenetic approaches. We employed transgenic mice expressing channelrhodopsin-2 (ChR2) in TRPV1-positive nociceptive neurons. In situ hybridization revealed that compared to males, females had a significantly larger portion of small-sized (100-200 μm2) Trpv1+ neurons in dorsal root ganglion (DRG). Blue light stimulation of a hindpaw of transgenic mice induced intensity-dependent spontaneous pain. At the highest intensity, females showed more intense spontaneous pain than males. Intraplantar injection of IL-23 (100 ng) induced mechanical allodynia in females only. Furthermore, intraplantar injection of IL-23 potentiated blue light-induced pain in females but not males and intrathecal injection of IL-23 potentiated low-dose capsaicin (500 ng) induced spontaneous pain in females but not males. While IL-23 expression was comparable in DRG macrophages of both sexes, intrathecal injection of IL-23 induced significantly greater p38 phosphorylation (marker of nociceptor activation) in DRGs of female mice than male mice. Finally, estrogen and chemotherapy co-application increased IL-23 secretion and estrogen and IL-23 co-application increased IL-17A release in THP-1 human macrophages. These findings validate that IL-23 produces female-dominant pain in mice. Our study has also provided new insight into cytokine-mediated and sex-dependent macrophage-nociceptor interactions in mice.